PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK MELALUI APLIKASI TIKTOK SHOP PADA MAHASISWA UIN STS JAMBI TAHUN 2023 - Devina Pramesti Pangindaran; Putri Apria Ningsih; Rohana Rohana (CV. Aksara Global Akademia, 2024)
This study aims to determine and analyze the effect of price and promotion on consumer purchasing decisions. This study used a quantitative approach and the data analysis method used was multiple linear regression analysis. The sample used in this study was 100 UIN Jambi students. The results of the partial price study had no influence and were not significant on consumer purchasing decisions, obtained a significance value of 0.688 > 0.005 calculated value (-0.403) < smaller than ttable (1.985). And promotion has a positive effect on consumer purchasing decisions, a significant value of 0.000 < 0.005 is obtained and t calculate > t table which is 6.873 > 1.985. Based on the results of the F test, it can be known that the significance value for the effect of price (X1) and promotion (X2) simultaneously on product purchase decisions (Y) is 0.000 < 0.05 and the value of Fcalculate > Ftable (46.886 > 3.09). So it can be concluded that Ho was rejected which means that there is a significant influence between price and promotion simultaneously together on consumer purchasing decisions on Tiktok Shop. The value of Adjusted R Square (R2) which means that consumer purchasing decisions are influenced by price (X1) and promotion (X2) on consumer purchase decisions (Y) has an influence of 48.1% and the remaining 51.9% is influenced by other variables that are not studied in this research model and the most dominant influential variable is promotion (X2).